Kuantifikasi Protein HAS2, PTX3, BCL2 dan BAX dalam Sel Kumulus Oosit Matur (MII) dan Imatur (MI) Pada Pasien Bayi Tabung - Dewi, Ni Putu Sri Risa; Wiratmini, Ngurah Intan; Sudiman, Jaqueline (Metamorfosa: Journal of Biological Sciences; Vol 9 No 2 (2022), 2022)
Oocyte developmental competence is one of the determining factors that in?uence the outcomes of an IVF cycle regarding the ability of a female gamete to reach maturation and be fertilized. A non-invasive approach using proteomic analysis of oocyte cumulus cells (CCs) can be used as a method to predict oocyte competence and viability that could potentially function as molecular predictors for IVF program prognosis. Our study was aimed at quantifying protein markers (HAS2, PTX3, BCL2 and BAX) that are expressed in human CCs between mature (MII) and immature (MI) oocytes. This research is an analytic observational study. Twelve samples of CCs from mature (MII) and immature (MI) oocytes were collected after ovum pick up from patients undergoing ICSI. CCs samples were isolated using an ultrasonicator and protein expressions were quantified using ELISA method. The Mann-Whitney test was used to compare the protein expressions from CCs between mature and immature oocytes. The results showed HAS2, PTX3 and BCL2 proteins expressions was increase in CCs from mature oocytes but had no significant effect compared to CCs from immature oocytes, however, BAX protein expression was significantly higher (P<0.05) in CCs from immature oocytes which CCs from mature oocytes. This present study shows that BAX proteins could be used as markers for oocyte quality and maturation. Key words : ELISA, maturation, proteins marker, cumulus cells (CCs)